Individuality is everything: Autonomous femininity in MySpace mottos and self-descriptions - Dobson, Amy (Routledge, 2012)
This article explores some popular constructions of young femininity on MySpace profiles through an examination of the affirmative or inspirational-style mottos and self-descriptions commonly posted on a sample of 45 public profiles maintained by Australian women aged between 18 and 21. In these texts self-esteem, self-worth, and self-determination are expressed in markedly uncompromising tones. Such textual expressions, I argue, may indicate an internalization on the part of young women of neo-liberal discourses of individualization. At the same time, the mottos discussed also suggest that traits and characteristics besides sexiness are central to young women's online, socially moderated self-constructions. That is, the demonstration of a bold attitude and a fearless sense of autonomous self-definition also appear to be important aspects of feminine performativity on the profiles viewed, which is significant in light of recent panic around young women and sexualization. © 2012 Taylor & Francis.